Tumor initiating cells escape tumor immunity via CCL8 from tumor-associated macrophages in mice - Shuang Chen; Chen‐Song Huang; Kang Li; Maosheng Cheng; Caihua Zhang; Jianqi Xiong; Guoli Tian; Ruoxing Zhou; Rongsong Ling; Xiaochen Wang; Gan Xiong; Zhihui Zhang; et al. (2025)
Tumor-initiating cells (TICs) play a key role in cancer progression and immune escape. However, how TICs evade immune elimination remains poorly characterized. Combining single-cell RNA sequencing (scRNA-seq), dual-recombinase-based lineage tracing, and other approaches, we identified a WNT-activated subpopulation of malignant cells that act as TICs in vivo. We found intensive reciprocal interactions between TICs and immune regulatory tumor-associated macrophages (Reg-TAMs) via GAS6-AXL/MERTK signaling pathways, which facilitated the immune escape of TICs. Our study employed chemical inhibitors and Axl/Mertk conditional double knockout mice to demonstrate that inhibiting the interaction between TIC-derived GAS6 and AXL/MERTK in Reg-TAMs reactivated anti-tumor immune responses. We identified CCL8 as a critical mediator of the GAS6/AXL/MERTK pathway, primarily by inhibiting regulatory T cell (Treg) infiltration into the tumor. Furthermore, the AXL/MERTK signaling blockade sensitized tumor cells to anti-PD-1 treatment. Thus, we elucidated a detailed mechanism by which TICs evade tumor immunity, providing insights into strategies to eradicate TICs that escape conventional immunotherapy.